2014
DOI: 10.1155/2014/641814
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation, Chemical Characterization, and Antimicrobial Activity of Mexican (Lippia graveolensH.B.K.) and European (Origanum vulgareL.) Oregano Essential Oils

Abstract: The effect of solvent polarity (methanol and pentane) on the chemical composition of hydrodistilled essential oils (EO's) of Lippia graveolens H.B.K. (MXO) and Origanum vulgare L. (EUO) was studied by GC-MS. Composition of modified starch microencapsulated EO's was conducted by headspace-solid-phase microextraction (HS-SPME). The antimicrobial activity of free and microencapsulated EO's was evaluated. They were tested against Salmonella sp., Brochothrix thermosphacta, Pseudomonas fragi, Lactobacillus plantarum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 34 publications
1
41
1
4
Order By: Relevance
“…Antimicrobial activity was evaluated following the methodology of Hernández-Hernández [23]. Briefly, 10 mL of trypticase soy agar (0.8% w/v, Bioxon, Cuautitlan, México) was inoculated with 500 µL of L. innocua solution (10 7 CFU/mL), subsequently poured onto plates containing solidified agar (1.5% w/v).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Antimicrobial activity was evaluated following the methodology of Hernández-Hernández [23]. Briefly, 10 mL of trypticase soy agar (0.8% w/v, Bioxon, Cuautitlan, México) was inoculated with 500 µL of L. innocua solution (10 7 CFU/mL), subsequently poured onto plates containing solidified agar (1.5% w/v).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…This problem may be overcome through the microencapsulation of essential oils, in which coating a micro-drop of essential oil is carried out with different solid compounds [10]. The purpose of microencapsulating an essential oil is to slow its release without losing its biological properties [11][12][13]. Microencapsulation is applied broadly for food preservation from food borne bacteria and fungi [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the antibacterial and fungicidal properties of thymol (Andrade-Ochoa et al, 2015;Džamić et al, 2015;Hernández-Hernández et al, 2014). For this reason, this compound has received the attention of the food industry, thymol having been used as an antimicrobial agent and authorized by the Food and Drugs Administration (FDA) of the USA as generally recognised as safe (GRAS).…”
Section: Introductionmentioning
confidence: 99%